An analysis of paramedic out-of-hospital endotracheal intubation success in Johannesburg, South Africa - Botha, Martin John (My University, 2012)
Study objective: The aim of this study was to describe and analyse the success of endotracheal tube (ETT) placement when performed by paramedics in the out-of-hospital setting in Johannesburg, South Africa. Design: A prospective, observational study design with a consecutive convenience sample was used to analyse the prevalence of unrecognised mal-positioned ETTs by ALS paramedics. Setting: The ETT position was evaluated by the receiving medical practitioner in patients arriving at eight different urban, public and private, Johannesburg emergency departments (EDs) after being intubated by paramedics from multiple, both public and private – emergency medical services (EMS) agencies out-of-hospital. The study is set in a developing context where EMS systems vary considerably in terms of clinical governance, paramedic experience and qualification, and resources. Patients: All patients who arrived at Johannesburg EDs who had been intubated by paramedics out-of-hospital regardless of indication, aetiology or age, were included in the convenience sample. Methods: The main outcome measure was the unrecognized misplaced intubation rate which was recorded via routine methods by the receiving medical practitioner immediately upon arrival of the intubated patient at the ED. Findings were compared with international values. The use of endotracheal intubation confirmatory devices, both by paramedics and ED medical practitioners, was also reported. Main results: Of the 100 patients who were intubated out-of-hospital, 2 (2%; 95 CI 0.4% – 7.7%, p < 0.0001) arrived with unrecognised oesophageal ETT misplacements, and the ETT cuff was found to be in the pharynx, above the vocal cords in 1% of the sample. Thus, unrecognised mal-positioned intubations were detected in a total of 3 of 100 cases (3%; 95 CI 0.8% – 9.2%, p < 0.0001). Right main bronchus positioning occurred in 9 (9%) of cases. Paramedics reported the use of auscultation of the chest and stomach in 98% of the sample to confirm ETT placement, direct laryngoscopy in 22%, end-tidal carbon dioxide detection (ETCO2) in 19%, and pulse oximetry in 12% of patients. None of the misplaced ETTs had ETCO2 verification used out-of-hospital. ETT confirmation strategies by ED medical practitioners included auscultation of the chest and stomach in 97% of cases, direct laryngoscopy in 33%, and use of capnography to detect ETCO2 in only 4% of out-of-hospital intubated patients. Conclusions: This, the first known study to evaluate endotracheal intubation placement by EMS personnel in South Africa, found an overall 3% rate of misplaced ETTs (2 oesophageal and 1 hypopharyngeal), similar to several previous investigations, and much less than earlier studies. The findings of this study have important implications for South African EMS policy and practice. Based on the findings of this study, it seems reasonable to recommend that in a resource-limited, developing country where expensive ETCO2 is not readily available, the out-of-hospital ETT position should, at very least, be confirmed via auscultation, direct laryngoscopy and subjective clinical methods. Despite showing a statistically significant reduction in ETT misplacement rates when compared to international studies in similar settings, the results of this Johannesburg study are alarming and cause for concern, since any misplacement of an ETT in a critically ill or injured patient is calamitous with the potential for increased morbidity and mortality.
Keywords: Emergencies